2010
DOI: 10.1086/652400
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity toChlamydia trachomatisGenital Infection: Evidence from Human Studies

Abstract: Background Some screening and treatment programs implemented to control genital Chlamydia trachomatis infections and their complications have shown initial reductions in infection prevalence followed by rises to pre-program levels or higher. One hypothesis is that treatment shortens duration of infection, attenuates development of protective immunity and thereby increases risk of re-infection. Methods A literature review was undertaken to assess evidence supporting the concept of protective immunity, its cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
85
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 95 publications
(105 reference statements)
10
85
1
Order By: Relevance
“…Younger age and pregnancy were independently associated with a higher bacterial load of C. trachomatis and younger age and having had more than one sexual partner in the last 6 months with a higher load of N. gonorrhoeae. The same relation with age (for C. trachomatis) in several NAAT studies has been described before and might be due to changes in the cervical epithelium or to younger women being more sexually active and exhibiting riskier behavior or might reflect acquired immunity in adults (28)(29)(30). There were several limitations to our study.…”
supporting
confidence: 57%
“…Younger age and pregnancy were independently associated with a higher bacterial load of C. trachomatis and younger age and having had more than one sexual partner in the last 6 months with a higher load of N. gonorrhoeae. The same relation with age (for C. trachomatis) in several NAAT studies has been described before and might be due to changes in the cervical epithelium or to younger women being more sexually active and exhibiting riskier behavior or might reflect acquired immunity in adults (28)(29)(30). There were several limitations to our study.…”
supporting
confidence: 57%
“…We tested the hypothesis that the anti-chlamydial immune effectors induced during infections that produce complications are qualitatively or quantitatively different from non-complicated infections. Our results are corroborated by previous reports on the analysis of anti-chlamydial cytokine response by Peripheral Blood Leukocytes (PBL) from infected women with and without tubal symptoms that indicated that chlamydial control in humans is Th1-mediated, involving IFN-γ; and that infections with complications are characterized by Th2 response marked with secretion of IL-4, IL-5 and IL-10 [28][29][30][31]. Accordingly, we found significantly greater levels of the Th1-type cytokines, TNF-α, IFN-γ and IL-17 in sera from infected mice that were protected from infertility than infected animals that developed infertility; and there were significantly greater levels of the Th2-type cytokines, IL-5 and IL-10, in the serum of infected mice that developed infertility than mice protected from infertility.…”
Section: Discussionsupporting
confidence: 91%
“…However, the results are similar to the cytokine measurements following antigen stimulation of PBL previously reported [21,30]. The key finding from this study therefore is that the results from analysis of immune profiles after genital chlamydial infection revealed that in experimental animals protection from tubal pathologies and infertility is associated with a predominantly Th1 response, which is corroborated by previous human studies using antigen-specific cytokine response by PB to chlamydial antigens [21,30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations